Persepsi Masyarakat tentang Penggantian Nama Anak Untuk Kesehatan: Studi Komparatif Ulama Mazhab dan Hukum Adat - Annuari, Handini; Syarif, Muh. Rasywan; Abdul Qayyum, Abdul Rahman Hi. (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to describe and analyze the renaming of children for health, from the perspective of Islamic law and customary law which is then linked to what happened in Ex. Bontoparang, Kec. Parangloe, Kab. Gowa, South Sulawesi. In answering the above problems, the author uses Field Research, namely research that raises data and problems in the field (location of research). The sources of data obtained include primary data and secondary data. This study uses a type of qualitative research using an empirical juridical approach, namely to find out how a law is implemented and how the process is enforced. The results of this study indicate that in Ex. Bontoparang, Kec. Parangloe, Kab. Gowa, South Sulawesi, there is a public belief that if a child is often sick, his name will be changed. Scholars disagree about the name that is most loved by Allah swt., some argue: the name of the prophets while the majority of scholars agree that the name most loved by Allah swt is the name that is leaned on (iḍāfaāt) to Asmā al-ḥusnā. Myth or belief in something that is beyond reason is something that has long existed in Indonesian society, especially in South Sulawesi. In interviews conducted by researchers, almost the majority of respondents stated and understood that they did not really think about whether changing their name due to health was a myth or not. Because they think that as long as it is good then it is legal to do and practice it. With good intentions and goals, they take the initiative to change their name or their child to make it better than before. Those who were sick before are healthy.